Scanning Tunneling Microscopy and Spectroscopy of Layered Materials - Zhussupbekov, Kuanysh (Trinity College Dublin. School of Physics. Discipline of Physics, 2021)
In this thesis, the atomic and electronic structures of several layered materials have been investigated by a host of surface-sensitive techniques. The core of this work focuses on layered single crystals, such as Bi(111) and GeTe(111), and Pt based transition metal dichalcogenides (TMDs) investigated primarily by scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS). In this thesis, a theoretical and experimental study of the two-dimensional (2D) defects on the surface of Bi(111) and the states that they induce is presented. Bi crystals cleaved in ultra-high vacuum (UHV) at low temperature (110 K) and the subsequently ion-etched surface are investigated by low-energy electron diffraction (LEED), X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), STM and STS techniques in combination with density functional theory (DFT) calculations. STS measurements of cleaved Bi(111) reveal that a commonly observed bilayer step edge has a lower density of states (DOS) around the Fermi level, as compared to the atomically-flat terrace. Following ion bombardment, the Bi(111) surface reveals anomalous behaviour at both 110 K and 300 K. Surface periodicity is observed by LEED and a significant increase in the number of bilayer step edges and energetically unfavourable monolayer steps were observed using STM. It is suggested that the newly exposed monolayer steps and the type A bilayer step edges result in an increase to the surface Fermi density as evidenced by UPS measurements and the Kohn-Sham DOS. In the same chapter, the atomic and electronic properties of a GeTe(111) bulk single crystal was investigated. Two types of domain boundaries were observed, one of them being similar in structure to the van-der-Waals gap in layered materials. This structure is responsible for the formation of surface domains with preferential Te termination (~68 %). Breaking of the covalent bonds (Ge termination) was observed using STM. The lateral dimensions of the surface domains are in the range of ~10-100 nm, and both Ge and Te terminations reveal no reconstruction determined by STM and LEED. Additionally, two types of point defects were resolved by STM and their electronic properties examined by STS. Turning to Pt-based TMDs, a combination of STM and STS was employed to investigate the properties of layered PtS2, synthesised via thermally assisted conversion (TAC) of a metallic Pt thin film. STM measurements reveal the 1T crystal structure of PtS2, and the lattice constant was determined to be 3.58±0.03 AA. STS allowed the electronic structure of individual PtS2 crystallites to be directly probed and a bandgap of ~ 1.03 eV was determined for a 3.8 nm thick flake at 77 K. These findings substantially expand understanding of the atomic and electronic structure of PtS2 films. Prior to STM/STS measurements the quality of synthesised TAC PtS2 was analysed by XPS, X-ray diffraction (XRD) and Raman techniques. An experimental and theoretical investigation of the electronic structure of PtSe2 step edges was performed. Through performing STM and STS measurements, in combination with DFT calculations, differences between the electronic properties of PtSe2 step edges (edge states) and atomically-flat terraces were highlighted. Moreover, a distinct dependence of the bandgap on the thickness of PtSe2 flakes was demonstrated. Prior to the STM and STS investigation, the quality of PtSe2 films was characterised by Raman and XPS spectroscopy. These insights could provide an effective way for optimizing the interface contact and tunability of the bandgap. The properties and performance of 2D materials can be greatly affected by point defects. In this thesis, an experimental and theoretical investigation of point defects on and near the surface of PtTe2 is presented. Using STM and STS measurements, in combination with DFT, five common surface and sub-surface point defects are identified and characterised. The influence of these defects on the electronic structure of PtTe2 is explored in detail through grid STS measurements and complementary DFT calculations. These findings could be of significance to future efforts to engineer point defects in PtTe2, which is an interesting and enticing approach to tune the charge-carrier mobility and electron-hole recombination rates, as well as the site reactivity for catalysis.
APPROVED
Keywords: Microscopy; Spectroscopy